Efficacy of long-term outcomes and prosthesis satisfaction in war related above knee amputees of Tehran - Elham Esfandiari; Mehdi Masoumi; Amir Yavari; Hasan Saeedi; Mostafa Allami (Vesnu Publications, 2011)
Background and purpose: Amputation is one of the most deleterious events that one may experience throughout his/her life. Gait patterns adopted by Amputees with prosthesis can cause such various types of pain as back pain, hip joint pain and contralateral pain. Knowledge about existing problems associated with amputated limb can be useful in making decisions about appropriate treatment plans and rehabilitation programs for these patients. The aim of this study was to evaluate long-term outcomes and prosthesis satisfaction in persons with war-related above-knee amputations. Material and methods: Sixty-one Iranian subjects with above knee amputation were requested to fill out the Persian version of Prosthesis Evaluation Questionnaire (PEQ) and to judge whether they were satisfied with their current prosthesis. Results: Phantom sensation, phantom pain, residual limb pain, lateral limb pain and back pain was respectively reported in 88.5%, 77%, 36.1%, 33% and 72.1% of the subjects. Moreover, it became evident that 19.67% of the subjects were truly satisfied with their current prosthesis. Conclusion: According to study results, phantom sensation, phantom pain, back pain, residual limb pain and pain in the lateral limb are the most prevalent outcomes of war related amputations. Satisfaction rates were higher than moderate in more than half of the patients studied. Key words: limb loss, phantom pain, phantom sensation, satisfaction